The Impact of Auditors' Professional Judgment and the Whistleblowing System on the Disclosure of Financial Management Fraud in Local Government: Evidence from BPK Representatives in Central Java, Indonesia. - Fikriyah, Nassol; Andriyanto, Irsad (IAIN Kudus, 2025)
This study examines the increasing incidence of corruption in Indonesia, with a focus on the roles of auditors' professional judgment and the whistleblowing system in detecting financial management fraud within local governments. Using a quantitative approach, data were collected from 38 auditors of the Central Java Audit Board (BPK) through purposive sampling and analyzed using IBM SPSS Statistics. The results demonstrate that both professional judgment and the whistleblowing system have significant positive effects on fraud disclosure. These findings underscore the crucial need to enhance oversight mechanisms and advocate for additional research on factors that influence fraud disclosure, particularly in light of the decline in the Anti-Corruption Behavior Index (IPAK) in 2024. The study contributes to enhancing the understanding of fraud detection processes in public sector auditing and provides actionable insights for policymakers and auditing institutions to improve transparency and accountability.